High fidelity estimates of paratransit energy consumption from per-second GPS tracking data. (May 2023) - Hull, Christopher; Giliomee, J.H.; Collett, Katherine A.; McCulloch, Malcolm D.; Booysen, M.J.
Abstract: Paratransit, in particular the minibus taxi, is the mainstay of public transport in sub-Saharan Africa. These vehicles are often second-hand, ageing, fuel inefficient, and expensive to operate - issues that electrification can ameliorate. However, modeling and planning large-scale transitions to electric paratransit require reliable estimates of vehicle energy consumption. This paper provides such estimates by applying a vehicle kinetic model to per-second GPS data gathered on minibus taxis. Data include 62 trips across three routes with different driving conditions near Stellenbosch, South Africa. We find a range of energy consumption from 0.29 to 0.51 kWh/km (mean = 0.39 kWh/km). Past estimates in literature relied on per-minute GPS data, which we show leads to inaccurate energy consumption estimates. We recommend new kWh/km values for modeling vehicle operations and grid impact, and discuss how future work can utilize our analysis to advance the transition to electric paratransit sub-Saharan Africa. Graphical abstract: Highlights: Highest fidelity kWh/km estimates for paratransit in sub-Saharan Africa to date. Urban, hilly, and inter-city driving conditions are investigated. 0.29–0.51 kWh/km (mean = 0.39 kWh/km), depending on driving condition. Specific kWh/km recommendations for usage in operations planning and grid impact. Per-minute data fails to capture effect of micro-mobility patterns on kWh/km.